Scenario development for improving supply chain performance using the system dynamics approach - Santoso, Imam; Sa'adah, Miftahus; Asmaul Mustaniroh, Siti (International Journal of Engineering and Technology, 2019)
Supply chain management integrates the entire business process of a product from upstream to downstream with the aim of delivering products to consumers in a timely manner and precise quantity without overriding profit. The application of dynamics systems is aimed to provide a holistic view of the system and to identify how interrelationship affects the system as a whole. System dynamics approach is used to analyze the efforts to improve performance. Besides being used as an analysis related to the model, system dynamics can also be used to formulate effective policy related to the profit distribution in case study of bell pepper supply chain. In this study, several scenarios were used as references to improve bell pepper supply chain performance in Regency X. The stake holders in the supply chain were farmer, middleman, and wholesaler. There were three sub-models used in system dynamics, namely the sub-model farmer, middleman, and wholesaler. The model in the system dynamics was then developed to find out the best scenario in improving the performance of bell pepper supply chain. The scenario developed consisted of 4 scenarios in which scenario 1 became the basic scenario as the comparison of simulation results. Then, Scenario 2 was a Supply-Demand arrangement to reduce losses obtained at the level of middleman and wholesaler. The policy of Scenario 3 was warehouse procurement, which was a model improvement scenario in Scenario 3. Lastly, Scenario 4 was an increase in the level of demand / market expansion without an increase in the number of production. The highest total supply chain profit from the four scenarios was in Scenario 3, while the lowest was Scenario 2.Â Â Â